Twenty-four seconds from now... : a love story - Reynolds, Jason (Atheneum, 2024)
"Neon is freaking out... Twenty-four months ago, a feisty, fangy little dog chased him around a cemetery. Not Neon's finest moment. Except, chasing the dog chasing Neon was... Aria. Way more than fine. Twenty-four weeks ago, Neon and Aria, who are most definitely a THING, are thinking about connecting on a whole other level. Twenty-four days ago, Neon tries not to die of embarrassment in the diner as his mother gives him a whole lot of things to think about before... before... Twenty-four minutes ago, Aria's parents are out for the evening, and Neon is in, with a bouquet of chicken tenders (Aria's most favorite thing besides Neon!) as tonight's the night... Right now, Neon is freaking out. Photo of the feisty, fangy dog staring fiercely at him. And Neon & Aria aren't going to be doing anything if Neon can't get out of his head full of what-if what-if what-ifs... and trust that his love for his girl is enough." --